A New Method for the Calibration of Site-Related Response Spectra. (30th July 2022) - Han, Xin; Yang, Shun; Bo, Jingshan; Chang, Chaoyu; Guo, Mei; Cai, Yimeng
Abstract : The calibration of response spectra is an important issue that needs further research in engineering earthquake resistance. This paper proposes an improved calibration method for site-related response spectra. The seismic acceleration response spectra are statistically analyzed in the random period bands in the form of regression analysis, and the fitting indices in each frequency band under 11 different functions are given. Accordingly, the best fitting function for each period band is determined. Combined with a genetic algorithm, the control parameters of the seismic acceleration response spectrum are calibrated according to the determined new design spectral shape. After comparing the calibration results with the proposed piecewise results, a new calibration model of the three-section curve expression is proposed by improving the piecewise standard until the calibration results are identical to the proposed period point. The accuracy of the proposed calibration method is validated against the other four available methods using Qian'a earthquake records and actual engineering examples. The research results show that the site-related response spectrum calibration method given in this paper objectively reflects the spectrum characteristics of the site-related response spectrum. The proposed method may have a certain reference value for the calibration of the site-related response spectrum.